Prisoner exposure to nature: Benefits for wellbeing and citizenship. (February 2019) - Reddon, John R.; Durante, Salvatore B.
Abstract: The direct or indirect experience of crime can cause individuals to feel vengeful against the perpetrator(s). The prison system reflects this sentiment by creating austere environments that are dehumanizing, punitive, and hopeless. Prisons are, therefore, environments in which retribution and punishment take priority over rehabilitation. Frequently, prisoners are believed to be untreatable because of their antisocial orientation. However, several factors influence an antisocial orientation such as socioeconomic status, family of origin, and mental health. The ubiquitous nothing works misbelief has resulted in prisoner marginalization and increased recidivism because of insufficient treatment. In 2015, 10 million individuals were incarcerated worldwide with around 30 million circulating through prisons each year. The prison environment decreases prisoner life expectancy and overall health. Sadly, prisoner benefits from treatment post-incarceration dissipate after 3–6 months and many prisoners die by suicide or drug overdose. Prison overpopulation, as well as poor outcome post-incarceration, requires more effective treatment. We hypothesize that Prisoner Exposure to Nature (PEN) can transform prisons into environments that are conducive to maintaining and improving physical and mental health. In prior work we proposed the continuum Nature Exposure Sufficiency (NES) versus Nature Exposure Insufficiency (NEI). Prisons are impoverished environments that limit Nature Exposure (NE) which results in NEI. Individuals experience fluctuations in mental and physical health as a result of NEI. Numerous studies have shown that direct and indirect NE can improve mood, physical health, and facilitate connectivity with self and society. It is necessary to consider ways in which we can incorporate NE for prisoner wellbeing. Additionally, it is crucial that prison personnel and prisoners develop a therapeutic/helping relationship (i.e., alliance) that is facilitated by friendliness and warmth to foster social change and citizenship. Many prisoners experience isolation and disconnection with society upon reentry. Given that most prisoners are eventually released into the community, we are obligated not to make them worse. Hence, it is important that prisons create programs that develop citizenship to engender prisoner volition to become positive and active citizens. We focus on the prison and prisoners, however our work is relevant to all total institutions (e.g., mental hospitals, nursing homes, schools, etc.). The prison system favors punishment and mass incarceration over treatment and decarceration. The deleterious effects of incarceration are clear and it is time to implement treatments based on the principles of PEN to improve prisoner wellbeing and citizenship.